Preparation method of titanium-based composite material with graphene-Ti double-communication structure
By constructing a graphene-Ti dual-connection structure in titanium-based composite materials, the problems of high-thermal conductivity titanium-based composite materials in the prior art are solved, and the thermal conductivity and strength of the material are significantly improved under low graphene content and reduced material cost.
Patent Information
- Application Number
- CN202510056180.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-14
AI Technical Summary
In the prior art, when preparing high-thermal conductivity titanium-based composite materials, a large amount of expensive high-thermal conductivity second phases, such as graphene, are required to add a high material cost, poor mechanical properties, and the utilization efficiency of the high-thermal conductivity second phase is limited and the improvement of thermal conductivity is relatively limited.
The titanium-based composite material preparation method adopts graphene-Ti dual-connection structure. A three-dimensional structure is prepared by establishing a titanium-based frame and selective laser melting technology. The oxide scale is then removed in hydrofluoric acid solution and ultrasonic cleaning is performed. Graphene nanosheets and Mg(NO3)2 are ultrasonicated in isopropanol to allow Mg2+ ions to be adsorbed on the graphene surface and dispersed uniformly. Graphene is deposited on the titanium-based frame by electrophoretic deposition technology, and graphene/Ti-based composite material is prepared by discharge plasma sintering process to achieve the formation of a dual-connection structure.
With extremely low graphene content, the thermal conductivity and strength of the composite material are significantly improved, and the utilization rate of the high thermal conductivity second phase is achieved, reducing the raw material cost of the material. With pure titanium as the matrix, the thermal conductivity is increased from about 12W/(m·K) to about 23W/(m·K), and the strength is also slightly improved.
Smart Images

Figure CN119876671A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a titanium-based composite material with a graphene-Ti dual-connected structure. Background Art
[0002] As my country's aerospace industry advances by leaps and bounds, the performance of aircraft is constantly upgraded, and the requirements for the materials of the hot end components on the surface of aircraft are becoming more and more stringent. Lightweight, heat-resistant and high-strength properties have become rigid needs. Discontinuously reinforced titanium-based composites (DRTMCs) have emerged and have gained a firm foothold in the field of structural materials for aerospace with their advantages of light weight, high specific strength and excellent creep resistance. In recent years, researchers have discovered a new path: adding nano-TiB whiskers with superior strengthening efficiency to DRTMCs. These whiskers are like "traffic controllers" in the microscopic world, which can effectively block dislocation movement and control grain boundary sliding in high-temperature environments, injecting a dose of "heart booster" into the room temperature and high-temperature strength of composite materials, greatly expanding the application of titanium-based composites.
[0003] However, a bottleneck problem faced by titanium-based composites in applications is that when titanium-based composites are used as hot-end components on the surface of aerospace, they will have intense friction with the air and generate a large amount of aerodynamic heat. Due to the low thermal conductivity of titanium-based composites themselves (about 6.5W / (m·K)), the heat in the titanium-based composites cannot be dissipated quickly, resulting in the problem of excessively high local temperature of the titanium alloy and softening failure. To overcome the above problems, at present, titanium-based composites mainly use thermal conductive coatings and thermal barrier coatings to alleviate the heat accumulation on the surface of the composites. However, the bonding force between the coating and the substrate is weak and easy to fall off, and it is difficult to achieve complete and uniform coating of the coating for components with complex shapes. Therefore, research based on improving the thermal conductivity of titanium-based composites has important engineering significance. In order to improve the transmission efficiency of phonons in the material, the grains in the material are required to be coarse and less distorted; while fine grains and large lattice distortion are beneficial to the strength of the composite material, which leads to the phenomenon of intrinsic inversion of thermal conductivity and strength. Therefore, it is also of great scientific significance to achieve the synergistic improvement of thermal conductivity and strength of titanium-based composites through organizational structure design.
[0004] As a new type of two-dimensional carbon material, graphene is widely used to improve the mechanical and thermal properties of metal-based composites due to its extremely high strength (about 130GPa) and thermal conductivity (about 5300W / (m·K)). However, in DRTMCs, due to the low thermal conductivity of the titanium alloy matrix itself and the large interfacial thermal resistance between graphene and the matrix, in order to significantly improve the thermal conductivity of the composite material, a large amount of graphene needs to be added to construct a continuous high thermal conductivity channel, which will destroy the connectivity of the matrix and is not conducive to the mechanical properties of the composite material. This has caused a bottleneck problem that makes it difficult to further improve the performance of graphene-enhanced DRTMCs.
[0005] In summary, in order to improve thermal conductivity, the existing technology for preparing high thermal conductivity titanium-based composite materials often requires the addition of a large amount of expensive high thermal conductivity second phases such as graphene and diamond, which leads to high composite material costs, low second phase utilization, and poor thermal conductivity-mechanical properties. Therefore, there is an urgent need for a new type of high thermal conductivity and high strength titanium-based composite material that can further improve the thermal conductivity and mechanical properties of the composite material while reducing the material cost. Summary of the invention
[0006] The present invention aims to solve the problem that in the prior art, when preparing high thermal conductivity titanium-based composite materials, a large amount of expensive high thermal conductivity second phases such as graphene and diamond need to be added, resulting in high cost and poor mechanical properties of the composite materials. At the same time, the above method has limited utilization efficiency of the high thermal conductivity second phase (the improvement of relative thermal conductivity per mass fraction of enhanced relative thermal conductivity, that is, the improvement of thermal conductivity divided by the mass fraction of graphene), and the improvement of the thermal conductivity of the composite material is also relatively limited. A method for preparing a titanium-based composite material with a graphene-Ti dual-connected structure is provided.
[0007] A method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure is specifically carried out in the following steps:
[0008] 1. Establish a titanium-based framework model for electrophoretic deposition of graphene according to actual needs, and then use the selective laser melting technology to prepare a titanium-based framework with a corresponding three-dimensional structure; put the prepared titanium-based framework with a three-dimensional structure into a hydrofluoric acid solution to remove the surface oxide scale, and then place it in alcohol for ultrasonic cleaning to remove impurities;
[0009] 2. Add graphene nanosheets and Mg(NO3)2 to isopropanol for ultrasonic treatment to make the graphene surface adsorb Mg 2+ ions and dispersed them uniformly in isopropanol to obtain graphene isopropanol dispersion;
[0010] 3. Fixing the titanium-based frame to the negative electrode of the power supply, fixing the iron plate to the positive electrode of the power supply, placing it in the graphene isopropanol dispersion for electrophoretic deposition, and obtaining a frame for electrophoretically deposited graphene;
[0011] Fourth, the frame of electrophoretic graphene deposition is placed in a graphite mold for spark plasma sintering, titanium-based powder material is poured into the graphite mold, and slightly vibrated to allow the composite powder to fully fill the inside of the titanium-based frame of the graphene deposition, and then spark plasma sintering is performed to prepare a graphene / Ti-based composite material;
[0012] 5. After the heat preservation is completed, the furnace is cooled to below 100° C. in a vacuum environment and taken out to achieve the preparation of a graphene-reinforced titanium-based composite material with a double-connected structure.
[0013] Beneficial effects of the present invention: The present invention realizes the distribution of the connected configuration of graphene in the titanium-based composite material, and at the same time, by changing the titanium-based framework structure used for electrophoretic deposition of graphene, the configuration of the connected graphene can be regulated. Under the premise of extremely low graphene content, the thermal conductivity and strength of the prepared composite material are greatly improved compared with the alloy, and the high utilization rate of expensive graphene nanosheets is achieved, reducing the raw material cost of high thermal conductivity titanium-based composite materials. With pure titanium as the matrix, the thermal conductivity of the prepared graphene / Ti-based composite material is increased from about 12W / (m·K) of pure titanium to about 23W / (m·K), which is nearly doubled, and the strength is slightly improved compared with the pure titanium matrix.
[0014] In order to overcome the problem that graphene and Ti will have serious interface reactions at high temperatures, resulting in the destruction of their structure and the loss of excellent thermal conductivity-mechanical properties, in order to obtain high-performance titanium-based composite materials that can be used in high-temperature environments, high-temperature titanium alloys can be selected as the matrix, and TiB reinforcement phases can be introduced into the material. At the same time, the graphene used in the present invention is surface modified, such as using W, Ni, Cu and other elements for surface modification. Experiments show that surface modification does not affect the electrophoretic deposition of graphene on the surface of the titanium-based framework. Using TA15 as the matrix, W element surface modified graphene is selected, and (TA15-1vol.%TiB) composite powder is filled, and a graphene / (TA15-TiB) composite material with a dual-connected structure is prepared according to the above method. Its tensile strength is 1050MPa, which exceeds the sintered and forged commercial TA15, while still retaining a fracture strain of about 0.03. When the content of graphene in the titanium-based composite material with a connected structure is less than 0.2wt.% (the total mass of graphene in the electrophoretic solution and the mass ratio of the sintered composite material are about 0.2wt.%, and after the electrophoresis is completed, some graphene still remains in the electrophoretic solution), the thermal conductivity exceeds 13W / (m·K), which is nearly 1 times higher than that of the alloy. Compared with the main high thermal conductivity titanium-based composite materials at this stage, the material designed by the present invention has a certain room temperature tensile plasticity, and the graphene utilization rate is greatly increased from 0.3-0.6W / (m·K) per mass fraction of graphene to about 30W / (m·K) per mass fraction of graphene. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The present invention is a process flow chart of a method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure;
[0016] Figure 2 This is a macroscopic morphology of the TA15 frame before electrophoretic deposition in Example 1;
[0017] Figure 3 This is a macroscopic morphology of the TA15 frame after electrophoretic deposition in Example 1;
[0018] Figure 4 This is a surface morphology of the frame after electrophoretic deposition in Example 1;
[0019] Figure 5 This is the surface morphology of the W-modified graphene nanosheets on the framework surface in Example 1;
[0020] Figure 6 for Figure 5 Corresponding W element distribution diagram;
[0021] Figure 7 This is a low-magnification SEM photograph of the dual-connected structure graphene-reinforced titanium-based composite material in Example 1;
[0022] Figure 8 This is a SEM photo of the graphene nanosheets surface-modified with W element in the composite material prepared in Example 1;
[0023] Fig. 9 for Figure 8 Corresponding W element distribution diagram;
[0024] Fig.10 1 is a comparison diagram of engineering stress-strain between the TA15 frame and the dual-connected structure graphene-enhanced titanium-based composite material in Example 1; wherein 1 represents the TA15 alloy prepared using the same process as the control group, and 2 represents the dual-connected structure graphene-enhanced titanium-based composite material;
[0025] Fig.11 This is a surface morphology of the graphene / Ti composite material prepared in Example 2;
[0026] Fig.12 This is the interface morphology of the graphene / Ti composite material prepared in Example 2;
[0027] Fig.13 is the C element distribution diagram corresponding to Example 12;
[0028] Fig.14 It is a comparison diagram of engineering stress-strain between a pure titanium frame and a dual-connected structure graphene-reinforced titanium-based composite material in Example 2; wherein 1 represents pure titanium prepared using the same process as a control group, and 2 represents a dual-connected structure graphene-reinforced titanium-based composite material. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0030] Specific implementation method 1: In this implementation method, a titanium-based composite material having a graphene-Ti dual-connected structure is prepared by the following steps:
[0031] 1. Establish a titanium-based framework model for electrophoretic deposition of graphene according to actual needs, and then use the selective laser melting technology to prepare a titanium-based framework with a corresponding three-dimensional structure; put the prepared titanium-based framework with a three-dimensional structure into a hydrofluoric acid solution to remove the surface oxide scale, and then place it in alcohol for ultrasonic cleaning to remove impurities;
[0032] 2. Add graphene nanosheets and Mg(NO3)2 to isopropanol for ultrasonic treatment to make the graphene surface adsorb Mg 2+ ions and dispersed them uniformly in isopropanol to obtain graphene isopropanol dispersion;
[0033] 3. Fixing the titanium-based frame to the negative electrode of the power supply, fixing the iron plate to the positive electrode of the power supply, placing it in the graphene isopropanol dispersion for electrophoretic deposition, and obtaining a frame for electrophoretically deposited graphene;
[0034] Fourth, the frame of electrophoretic graphene deposition is placed in a graphite mold for spark plasma sintering, titanium-based powder material is poured into the graphite mold, and slightly vibrated to allow the composite powder to fully fill the inside of the titanium-based frame of the graphene deposition, and then spark plasma sintering is performed to prepare a graphene / Ti-based composite material;
[0035] 5. After the heat preservation is completed, the furnace is cooled to below 100° C. in a vacuum environment and taken out to achieve the preparation of a graphene-reinforced titanium-based composite material with a double-connected structure.
[0036] This implementation is guided by the urgent need for high thermal conductivity titanium-based composite materials for hot-end components on the surface of aircraft, and aims to address the key scientific issue of thermal conductivity-strength inversion of composite materials. A graphene / (TA15-TiB) composite material with a dual-connected structure is designed to synergistically improve the thermal conductivity and strength of the composite material under the premise of low graphene content.
[0037] The structure of this embodiment can be customized according to the needs, and is not limited to a specific structure. The structure can be a cubic frame structure, a hexagonal honeycomb structure, a complex topological structure, etc.
[0038] In this embodiment, W-modified graphene is first electrophoretically deposited on a titanium-based frame, and then the frame is filled with (TA15-TiB) composite powder, and the preparation of a dual-connected graphene / (TA15-TiB) composite material is achieved through spark plasma sintering. The connected graphene not only improves the strength of the composite material, but also forms a "fast channel" for phonon transmission, thereby improving the thermal conductivity of the composite material; the nano-TiB whiskers in the matrix achieve the refinement of the composite material structure and the improvement of its strength; and the titanium-based frame can play a toughening role in improving the deformation ability of the composite material.
[0039] This embodiment uses the method of electrophoretic deposition of graphene to accurately construct a graphene network on a titanium-based framework, and then fills in TA15-TiB composite powder and sintering to form a graphene-Ti dual-connected structure. This unique architecture avoids the drawbacks of adding a large amount of graphene to improve thermal conductivity in traditional methods. In the past, the addition of a large amount of high thermal conductivity second phases such as graphene and diamond would inevitably increase costs and easily destroy the connectivity of the matrix. The dual-connected structure can build an efficient heat conduction path with a small amount of graphene, and the heat can be quickly conducted along the graphene network, thereby improving the thermal conductivity of graphene, and then improving the thermal conductivity, reducing the dependence on expensive high thermal conductivity phases, while reducing costs. Maintain the continuity of the material matrix, allowing the titanium alloy matrix and the reinforcement phase to work together to achieve a synergistic improvement in strength-thermal conductivity. The titanium-based framework prepared by selective laser melting technology provides customized three-dimensional structural support for graphene deposition and composite powder filling. Compared with the disorderly addition of high thermal conductivity phases, this framework allows graphene and composite powder to stay in their proper places, ensuring reasonable stress distribution when the material is subjected to force, enhancing the load-bearing capacity of the composite material and helping to improve mechanical properties.
[0040] In this embodiment, W is used to modify the graphene nanosheets and adsorb Mg 2+ ions and then evenly dispersed in isopropanol. The modification improves the stability of graphene itself, inhibits its adverse reaction with Ti at high temperature, and preserves the excellent thermal and mechanical properties of graphene. Evenly dispersed graphene can be integrated into the system more densely and evenly, avoiding local stress concentration and uneven thermal conductivity caused by agglomeration. In this way, even at low content, it can maximize its effect of enhancing thermal conductivity and mechanical properties, avoiding the traditional practice of destroying the connectivity of the matrix and damaging the mechanical properties due to excessive addition, and achieving the coordinated optimization of thermal conductivity and strength.
[0041] In this embodiment, the framework of electrophoretically deposited graphene and TA15-TiB composite powder are sintered by spark plasma sintering process. This process can achieve densification in a shorter time and at a lower temperature, reducing the damage to the microstructure of the material caused by long-term sintering at high temperature; inhibiting abnormal grain growth, maintaining the state of fine grains that is beneficial to strength, and improving thermal conductivity with the help of graphene network, avoiding the intrinsic inversion phenomenon caused by taking into account both thermal conductivity and strength in traditional processes, and achieving a synergistic improvement of the two. The vacuum furnace cooling process after insulation can reduce defects such as microcracks caused by thermal stress when the material is cooled, ensure the integrity of the material, make the heat conduction channel complete, and the internal structure stable, further consolidating the synergistic effect of thermal conductivity and mechanical properties of the composite material.
[0042] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the process parameters of the laser melting technology in step 1 are: laser spot size is 100 μm, the set printing layer thickness is 0.03 mm, the laser scanning interval is 90 μm, the laser power is 155 W, and the scanning speed is 1200 mm / s. The rest is the same as specific embodiment 1.
[0043] Specific implementation method three: This implementation method is different from specific implementation method one in that: the height of the titanium-based frame in step one is 3 to 9 mm, the frame diameter is 5 to 40 mm, the volume concentration of the hydrofluoric acid solution is 5 to 15%, and the pickling time of the hydrofluoric acid solution is 0.5 to 2 min. The rest is the same as specific implementation method one.
[0044] Specific embodiment 4: This embodiment differs from specific embodiment 1 in that: the graphene nanosheets in step 2 are graphene nanosheets or surface-modified graphene nanosheets; the thickness of the graphene nanosheets is 1 to 3 nm, and the sheet diameter is 2 to 3 μm. Other aspects are the same as specific embodiment 1.
[0045] Specific embodiment 5: This embodiment is different from specific embodiment 1 in that the mass ratio of graphene nanosheets to Mg(NO3)2 in step 2 is 1:1-2. The rest is the same as specific embodiment 1.
[0046] Specific embodiment 6: This embodiment is different from specific embodiment 1 in that the ultrasonic treatment time in step 2 is 0.5 to 1 hour. The rest is the same as specific embodiment 1.
[0047] Specific embodiment 7: This embodiment differs from specific embodiment 1 in that the concentration of graphene in the graphene isopropanol dispersion in step 2 is 0.5-3 mg / mL. Other aspects are the same as those of specific embodiment 1.
[0048] Specific embodiment 8: This embodiment differs from specific embodiment 1 in that the process parameters of electrophoretic deposition in step 3 are: electrophoretic voltage is 40-60V, and electrophoretic time is 20-80min. Others are the same as specific embodiment 1.
[0049] Specific embodiment 9: This embodiment differs from specific embodiment 1 in that the process parameters of spark plasma sintering in step 4 are: sintering temperature is 1000-1100° C., holding time is 3-10 min, and pressure is 60 MPa. Others are the same as specific embodiment 1.
[0050] Specific embodiment 10: This embodiment differs from specific embodiment 1 in that the titanium-based powder material in step 4 is titanium alloy powder or titanium-based composite powder, and the particle size distribution of the titanium-based powder material is 15 to 53 μm. Other aspects are the same as specific embodiment 1.
[0051] The following examples are used to verify the beneficial effects of the present invention:
[0052] Embodiment 1: A method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure is specifically carried out according to the following steps:
[0053] 1. A titanium-based frame model for electrophoretic deposition of graphene is established according to actual needs, and then a titanium-based frame with a corresponding three-dimensional structure is prepared by selective laser melting technology. In this embodiment, a diamond lattice structure that takes into account both thermal conductivity and mechanical properties is selected, and the material used is TA15 alloy; process parameters of laser melting technology: laser spot size is 100 μm, set printing layer thickness is 0.03 mm, laser scanning spacing is 90 μm, laser power is 155 W, and scanning speed is 1200 mm / s; the height of the titanium-based frame is 9 mm, and the frame diameter is 200 μm; the prepared titanium-based frame is placed in a hydrofluoric acid solution for pickling, then taken out of the acid solution, rinsed with alcohol, and placed in alcohol for ultrasonic cleaning; the volume concentration of the hydrofluoric acid solution is 5-15%, and the pickling time of the hydrofluoric acid solution is 0.5-2 min;
[0054] Second, W-modified graphene nanosheets with a thickness of 1-3 nm and a sheet diameter of 2-3 μm and Mg(NO3)2 were added to isopropanol and ultrasonicated for 0.5 h to allow the graphene surface to adsorb Mg 2+ ions and dispersed uniformly in isopropanol to obtain a graphene isopropanol dispersion; the mass ratio of W-modified graphene nanosheets to Mg(NO3)2 was 1:1; the concentration of graphene in the graphene isopropanol dispersion was 1 mg / mL;
[0055] 3. Fix the titanium-based frame to the negative pole of the power supply, fix the iron plate to the positive pole of the power supply, put it into the graphene isopropanol dispersion for electrophoretic deposition, and obtain the frame of electrophoretically deposited graphene; the process parameters of electrophoretic deposition are: electrophoretic voltage is 50V, and electrophoresis time is 40min;
[0056] Fourth, the frame of electrophoretic graphene deposition was placed in a graphite mold for spark plasma sintering, TA15-TiB composite powder was poured into the graphite mold, and the mold was slightly vibrated to allow the composite powder to be fully filled into the titanium-based frame of the deposited graphene, and then spark plasma sintering was performed to prepare the graphene / (TA15-TiB) composite material; the process parameters of the spark plasma sintering were: sintering temperature of 1100° C., holding time of 3 min, and pressure of 60 MPa; the volume fraction of TiB in the TA15-TiB composite powder was 1%, and the particle size distribution was 15 to 53 μm;
[0057] 5. After the heat preservation is completed, the furnace is cooled to below 100° C. in a vacuum environment and taken out to achieve the preparation of a graphene-reinforced titanium-based composite material with a double-connected structure.
[0058] The preparation of W-modified graphene nanosheets in this embodiment is specifically carried out according to the following steps:
[0059] 1. Graphene nanosheets with a particle size of 1 to 5 μm and a thickness of 5 to 20 nm are washed with distilled water and dried, and then ultrasonically dispersed in a hydrofluoric acid solution with a volume concentration of 10% for 30 minutes, so that the graphene is fully dispersed in the solution and fully contacted with HF to functionalize its surface. After the ultrasonic treatment, the graphene is washed with distilled water again and dried to obtain graphene with surface functionalization;
[0060] 2. Mechanically mix NaCl and KCl in a molar ratio of 1:1 to obtain a mixed salt;
[0061] 3. Mechanically mix the WO3 particles and the surface functionalized graphene at a molar ratio of 1:8 to obtain a mixed powder; spread the mixed powder on the bottom of a crucible, and cover the surface of the mixed powder with mixed salt to obtain a crucible containing the mixed salt and the mixed powder; the volume ratio of the mixed powder to the mixed salt is 1:2;
[0062] Fourth, the crucible containing the mixed salt and the mixed powder is placed in a heat treatment furnace, the reaction temperature is 1000°C, and the surface modification of graphene is carried out for 30 minutes under an argon atmosphere. The WO3 particles react with the graphene to reduce the W single substance, which nucleates and grows on the graphene surface, thereby achieving W surface modification. After the reaction is completed, the furnace is cooled to below 100°C under an argon atmosphere, and the crucible is taken out;
[0063] 5. The reactants in the crucible are taken out, rinsed with distilled water and filtered with filter paper to completely remove the salt in the mixed powder, and the graphene surface modified by the W element is separated and dried, thus completing the preparation of the W element surface modified graphene nanosheets by the molten salt method.
[0064] The tensile strength of the graphene / (TA15-TiB) composite material with a dual interconnected structure obtained in this embodiment is 1050MPa, which exceeds the sintered and forged commercial TA15, while still retaining a fracture strain of about 0.03. When the graphene content in the titanium-based composite material with an interconnected structure is less than 0.2wt.% (the total mass of graphene in the electrophoretic fluid and the mass ratio of the sintered composite material is about 0.2wt.%, and some graphene still remains in the electrophoretic fluid after the electrophoresis is completed), the thermal conductivity exceeds 13W / (m·K), which is nearly 1 times that of the alloy.
[0065] from Figure 2 It can be seen that there is no obvious deformation and cracks in the titanium-based frame, indicating that the selected printing parameters are reasonable and can achieve the preparation of titanium alloys with complex three-dimensional configurations. Figure 3It can be seen from the results that electrophoretic deposition can make graphene evenly adhere to the surface of complex three-dimensional frameworks, proving that the design and regulation of graphene configuration by electrophoretic deposition of graphene on the framework is scientific and feasible. Figure 4 and Figure 5 It can be seen that the graphene on the framework surface is evenly distributed, indicating that this method can introduce a graphene interconnected structure inside the titanium-based composite material, and the interconnected graphene is evenly distributed and has a uniform thickness; it proves that W-modified graphene can be evenly adsorbed on the surface of the titanium-based framework. Figure 6 It can be seen that the W-modified graphene is evenly distributed. Figure 7 It can be seen from the graphene-Ti dual-connected structure in the sintered material. Figure 8 and Fig. 9 It can be seen that graphene did not undergo serious interface reaction during the sintering process, characterizing the distribution of W elements and proving the existence of W-modified graphene. Fig.10 It can be seen that compared with TA15 alloy, the strength of the composite material is greatly improved, and it also has a certain room temperature plasticity. This shows that the composite material prepared by this method has excellent mechanical properties.
[0066] Example 2: A method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure is specifically carried out according to the following steps:
[0067] 1. A titanium-based frame model for electrophoretic deposition of graphene is established according to actual needs, and then a titanium-based frame with a corresponding three-dimensional structure is prepared by selective laser melting technology. In this embodiment, a cubic frame structure that takes into account both thermal conductivity and mechanical properties is selected, and the material used is pure Ti; process parameters of the laser melting technology: laser spot size is 100 μm, the set printing layer thickness is 0.03 mm, the laser scanning spacing is 90 μm, the laser power is 155 W, and the scanning speed is 1200 mm / s; the height of the titanium-based frame is 6 mm, and the frame diameter is 20 mm; the prepared titanium-based frame is placed in a hydrofluoric acid solution for pickling, then taken out of the acid solution, rinsed with alcohol, and placed in alcohol for ultrasonic cleaning; the volume concentration of the hydrofluoric acid solution is 5-15%, and the pickling time of the hydrofluoric acid solution is 0.5-2 min;
[0068] Second, graphene nanosheets with a thickness of 1-3 nm and a sheet diameter of 2-3 μm and Mg(NO3)2 were added to isopropanol and ultrasonicated for 0.5 h to allow the graphene surface to adsorb Mg 2+ ions and dispersed uniformly in isopropanol to obtain a graphene isopropanol dispersion; the mass ratio of graphene nanosheets to Mg(NO3)2 was 1:1; the concentration of graphene in the graphene isopropanol dispersion was 1 mg / mL;
[0069] 3. Fix the titanium-based frame to the negative pole of the power supply, fix the iron plate to the positive pole of the power supply, put it into the graphene isopropanol dispersion for electrophoretic deposition, and obtain the frame of electrophoretically deposited graphene; the process parameters of electrophoretic deposition are: electrophoretic voltage is 50V, and electrophoresis time is 40min;
[0070] Fourth, the frame of electrophoretic graphene deposition was placed in a graphite mold for spark plasma sintering, pure Ti powder was poured into the graphite mold, and slightly vibrated to allow the composite powder to fully fill the titanium-based frame of the deposited graphene, and then spark plasma sintering was performed to prepare graphene / Ti composite materials; the process parameters of spark plasma sintering were: sintering temperature of 1100°C, holding time of 3min, and pressure of 60MPa; the particle size distribution of pure Ti powder was 15-53μm;
[0071] 5. After the heat preservation is completed, the furnace is cooled to below 100° C. in a vacuum environment and taken out to achieve the preparation of a graphene-reinforced titanium-based composite material with a double-connected structure.
[0072] Fig.11 This is a surface morphology of the graphene / Ti composite material prepared in Example 2; it can be seen from the figure that the graphene in the composite material is continuously wrapped on the surface of the frame.
[0073] Fig.12 This is an interface morphology image of the graphene / Ti composite material prepared in Example 2; the thickness of the graphene layer in the image is about 2 microns.
[0074] Fig.13 This is the C element distribution diagram corresponding to Example 12; the C element distribution in the figure intuitively shows the specific distribution of graphene.
[0075] Fig.14 It is a comparison diagram of engineering stress-strain between a pure titanium frame and a dual-connected structure graphene-reinforced titanium-based composite material in Example 2; 1 represents pure titanium prepared using the same process, as a control group, and 2 represents a dual-connected structure graphene-reinforced titanium-based composite material; from the tensile curve, it can be seen that the composite material has excellent mechanical properties, the strength has been improved to a certain extent, and at the same time, an extremely high elongation is retained.
Claims
1. A method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure, characterized in that The preparation method of the titanium-based composite material having a graphene-Ti dual-connected structure is specifically carried out in the following steps:
1. Establish a titanium-based framework model for electrophoretic deposition of graphene according to actual needs, and then use the selective laser melting technology to prepare a titanium-based framework with a corresponding three-dimensional structure; put the prepared titanium-based framework with a three-dimensional structure into a hydrofluoric acid solution to remove the surface oxide scale, and then place it in alcohol for ultrasonic cleaning to remove impurities; 2. Add graphene nanosheets and Mg(NO3)2 to isopropanol for ultrasonic treatment to make the graphene surface adsorb Mg 2+ ions and dispersed them uniformly in isopropanol to obtain graphene isopropanol dispersion; 3. Fixing the titanium-based frame to the negative electrode of the power supply, fixing the iron plate to the positive electrode of the power supply, placing it in the graphene isopropanol dispersion for electrophoretic deposition, and obtaining a frame for electrophoretically deposited graphene; Fourth, the frame of electrophoretic graphene deposition is placed in a graphite mold for spark plasma sintering, titanium-based powder material is poured into the graphite mold, and slightly vibrated to allow the composite powder to fully fill the inside of the titanium-based frame of the graphene deposition, and then spark plasma sintering is performed to prepare a graphene / Ti-based composite material; 5. After the heat preservation is completed, the furnace is cooled to below 100° C. in a vacuum environment and taken out to achieve the preparation of a graphene-reinforced titanium-based composite material with a double-connected structure.
2. The method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure according to claim 1, characterized in that The process parameters of the laser melting technology in step 1 are: laser spot size is 100 μm, the set printing layer thickness is 0.03 mm, the laser scanning interval is 90 μm, the laser power is 155 W, and the scanning speed is 1200 mm / s.
3. The method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure according to claim 1, characterized in that The height of the titanium-based frame in step 1 is 3 to 9 mm, and the diameter of the frame is 5 to 40 mm; the volume concentration of the hydrofluoric acid solution is 5 to 15%, and the pickling time of the hydrofluoric acid solution is 0.5 to 2 min.
4. The method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure according to claim 1, characterized in that The graphene nanosheets described in step 2 are graphene nanosheets or surface-modified graphene nanosheets; the thickness of the graphene nanosheets is 1 to 3 nm, and the sheet diameter is 2 to 3 μm.
5. The method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure according to claim 1, characterized in that In step 2, the mass ratio of graphene nanosheets to Mg(NO3)2 is 1:1-2.
6. The method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure according to claim 1, characterized in that The ultrasonic treatment time in step 2 is 0.5 to 1 h.
7. The method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure according to claim 1, characterized in that The concentration of graphene in the graphene isopropanol dispersion in step 2 is 0.5-3 mg / mL.
8. The method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure according to claim 1, characterized in that The process parameters of electrophoretic deposition in step 3 are as follows: electrophoretic voltage is 40 to 60 V, and electrophoretic time is 20 to 80 min.
9. The method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure according to claim 1, characterized in that The process parameters of spark plasma sintering in step 4 are: sintering temperature of 1000-1100° C., holding time of 3-10 min, and pressure of 60 MPa.
10. The method for preparing a titanium-based composite material having a graphene-Ti dual-connected structure according to claim 1, characterized in that The titanium-based powder material in step 4 is titanium alloy powder or titanium-based composite powder; the particle size distribution of the titanium-based powder material is 15 to 53 μm.
Citation Information
Patent Citations
Graphene-reinforced titanium-based composite and preparation method thereof
CN104846227A
High-plasticity quasi-mesh-shaped structure titanium-based composite material and preparation method thereof
CN110343904A
Method based on laser sintering technique for preparing porous graphene-reinforced titanium-based nanocomposite material
WO2017070981A1